Potensi Sumber Daya Manusia Bidang Pariwisata di Kawasan Strategis Pariwisata Nasional Labuan Bajo, Nusa Tenggara Timur - Asep Syaiful Bahri; Fitri Abdilah (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2022)
The development of tourism sector in Labuan Bajo is expected to improve the welfare of the local community. The purpose of this research is to see the potential of human resources in the tourism sector, as well as to find out the opportunities and challenges of human resources for tourism midwives in Labuan Bajo. This study was designed with a qualitative descriptive approach to describe the various data obtained. Primary data is a factual approach to support secondary data that has been obtained earlier. The results of the study indicate that the development of labor absorption and the availability of labor is still a gap that must be considered to make Labuan Bajo a premium destination. The development of infrastructure and the tourism industry has not been matched by the development of human resources in Labuan Bajo. The findings of this study indicate that the problem of human resources in Labuan Bajo is not only about availability, but also about insufficient qualifications. For this reason, increasing the quality and quantity of labor availability needs to be accelerated by providing educational institutions and skills that are in accordance with destination development.